PERANAN PENGEMBANGAN PEMAHAMAN BUDAYA KONSUMEN DALAM PROSES INTERNASIONALISASI JASA PENDIDIKAN TINGGI DI INDONESIA - Budiprasetyo, Benedictus Karno (KINERJA, 2006)
This empirical research explores how the customer cultural awareness influences the management behavior of the higher education institution and the implementation of the internationalization strategy. Using the data form questionnaire filled by the Indonesian higher education management processed with PLS model estimation, it is found that the customer cultural awareness influence the implementation of the internationalization strategy indirectly through the management behavior. The results shows that the customer cultural awareness significantly influence (OSE:.54 and R2:.27) the management behavior and the management behavior significantly influence (OSE:.50 and R2:.28) the internationalization strategy implementation. This research result was a new phenomenon, since the previous research results shows a direct influence of the customer cultural awareness to the internationalization strategy implementation. The internationalization strategy implementation in the context of customer cultural awareness was depending on the management behavior as a key variable. This research result has its implication that the internationalization process of Indonesian higher education institution in the context of customer cultural awareness should be directed from the management behavior.Keywords : customer cultural awareness, higher education management, resource-basedapproach.